Podnikatelský plan pro založení video studia - Matulová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Předmětem diplomové práce je zpracování reálného podnikatelského plánu pro založení společnosti M. Matula Productions. Na základě teoretických poznatků, zpracovaných analýz vnějšího i vnitřního okolí podniku a průzkumu pomocí dotazníkového šetření je v návrhové části vytvořen konkrétní podnikatelský plán včetně finančního a marketingového plánu. Zpracovaný podnikatelský plán bude sloužit k rozhodnutí, zda s podnikáním začít či nikoliv.

The aim of this thesis is the creation of a real business plan for establishment of M. Matula Productions company. The business plan was created on the basis of theoretical knowledge, analyzes of external and internal environment of the company and also on the basis of a survey. Survey was led by a questionnaire. The business plan itself includes a financial and a marketing plan. It will be used to decide whether to start a business or not.
Business Plan for the Foundation of a Video Studio
Keywords: Podnikatelský plán; založení video studia; založení podniku; živnost; marketingový plán; finanční plán.; Business plan; videostudio foundation; setting up a business; trade; marketing plan; financial plan.